Choice of cerebral protection devices for carotid stenting - A. O. Korobkov; S. V. Volkov; S. A. Bagin; S. V. Lavrenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article analyzes a retrospective analysis of long-term results of 316 carotid stentings performed in patients with atherosclerotic stenosis of the extracranial parts of the internal carotid arteries using various types of cerebral protection devices – filters and proximal protection devices and their combinations. As a result of the analysis, we obtained data on the influence of the choice of cerebral protection devices on the risks of ischemic complications. The topic under consideration will be of interest to specialists in X-ray endovascular diagnostics and treatment, cardiovascular surgeons, and neurologists.